EconBiz — Meeting User Needs with New Technology - Pianos, Tamara (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Virtual libraries try to combine traditional library services with new document types and services. The first generation of virtual libraries mostly tried to offer services based on a library-centric view of information retrieval systems. New virtual libraries try to concentrate on user's needs, but this is often easier said than done. Restrictions like copyright laws, technical limitations and the like often make it difficult to meet user requirements. A number of studies documented these needs: easy-to-use, comprehensive yet focussed search, and easy access to print and online documents, subject specific, yet not too restricted to specific areas. The new EconBiz-portal, relaunched in August 2010, has a disciplinary focus on business and economics and related subjects. It includes about 6 million records from different databases. Based on search-engine technology Lucene/Solr, combined with a metadata framework developed by the ZBW, it allows fast, convenient and complex searches. The integration of the Standard-Thesaurus-for Economics supports researchers by suggesting key words and related terms. Information on the availability of the documents is also included. Documents can either be accessed online or ways are shown to material that is available in print only. Journals Online & Print, a service developed by the German Electronic Journals Library (EZB) and the German Union Catalogue of Serials (ZDB) is included to provide easy access to all forms of journals. In addition, services like an event calendar, a tutorial on how to find information and an online-reference desk help to cater to the user's complex needs. The new EconBiz-portal was developed by the ZBW in close cooperation with the USB Cologne. Major parts of the search engine framework were developed by a company specialized in information technology. This paper elaborates on the extraction of users' requirements from different studies, the deduction of functional requirements, and, finally, the implementation of the portal with all its ups and downs.